2015
DOI: 10.1590/1807-1929/agriambi.v19n1p21-26
|View full text |Cite
|
Sign up to set email alerts
|

Tamanho ótimo de parcela para avaliação do rendimento de grãos do girassol

Abstract: Propôs-se, neste trabalho, determinar o tamanho adequado de parcela para avaliação do rendimento de grãos do girassol, razão pela qual foi realizado, no período de maio a julho de 2011, um experimento no delineamento em blocos completos casualizados com 14 cultivares de girassol e 10 repetições. As parcelas foram constituídas de quatro fileiras com seis metros de comprimento espaçadas de 0,7 m e entre plantas de 0,3 m. A área útil da pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
(19 reference statements)
1
9
0
4
Order By: Relevance
“…Higher values of R 2 coupled with the significance of coefficients composing the model ensure higher MMC Ŷ = 48.35 *** X -0. reliability when determining the optimum plot size by the modified maximum curvature method (Figure 1). The best model fitting for this method was also reported by Sousa et al (2015), Donato et al (2008) and Viana et al (2002) for sunflower, banana and cassava, respectively.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Higher values of R 2 coupled with the significance of coefficients composing the model ensure higher MMC Ŷ = 48.35 *** X -0. reliability when determining the optimum plot size by the modified maximum curvature method (Figure 1). The best model fitting for this method was also reported by Sousa et al (2015), Donato et al (2008) and Viana et al (2002) for sunflower, banana and cassava, respectively.…”
Section: Resultssupporting
confidence: 68%
“…Several studies have been carried out on the use of the aforementioned methods for estimating the optimum plot size: modified maximum curvature method (Sousa et al, 2016;Cargnelutti Filhoet al, 2018;Guimarães et al, 2019), Hatheway's method (Sousa et al, 2016;Cargnelutti Filhoet al, 2016;Donato et al, 2018) andlinear response plateau regression (Sousa et al, 2015;Leonardo et al, 2014;Sampaio Filhoet al, 2019). These studies agree on the dependent relationship between plot size and CV of the characteristic; thus, characteristics with higher variability need larger unit areas to show significant differences between treatments (Donato et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The modified maximum curvature method is the most suitable for calculating the optimal plot size, not underestimating or overestimating the plot size as may occur in the linear plate and quadratic plate methods (SOUSA et al, 2015;DONATO et al, 2008;LOPES et al 2005). In studies with comparisons between the maximum curve method and the linear regression with plate, Sousa (2015), Brito et al (2012), Oliveira et al (2011) and Paranaíba et al (2009), found that the plot size obtained by the maximum curvature method was smaller than that obtained by the linear regression method.…”
Section: X = Smentioning
confidence: 99%
“…The soil heterogeneity index and the experimental material are factors that can alter the optimum plot size (STEEL et al, 1997). The size and heterogeneity of the BEU can alter the variance and the soil heterogeneity index, changing the optimum plot size.…”
Section: Introductionmentioning
confidence: 99%
“…Soil heterogeneity index values close to 1 indicate high soil heterogeneity, that is, low correlation between the adjacent plots (GOMEZ & GOMEZ, 1984), inflating the optimum plot size. Plot size studies following the protocol of MEIER & LESSMAN (1971) have been carried out to evaluate the number of ears, ear weight, and grain yield in wheat (LORENTZ et al, 2007); grain yield evaluation of sorghum (BRUM et al, 2008); comparison of estimation methods of optimum plot size in maize (CARGNELUTTI FILHO et al, 2011); and evaluation of grain yield in sunflower (SOUZA et al, 2015), which reveals the importance of this method for its wide use in research.…”
Section: Introductionmentioning
confidence: 99%